Analysis of bioactive compounds, antioxidant activity, and acute toxicity test of black garlic (Allium sativum L.) - Moch. Saiful Bachri; Muhammad Ma'ruf; Hasna Tsamarah; Daru Estiningsih; Prasasti, Dian; Danang Prasetyaning Amukti; Sapto Yuliani; Vivi Sofia (Pharmaciana, 2025)
Black garlic is obtained through a controlled fermentation process that alters its color, aroma, and flavor while enhancing its concentration of bioactive compounds. This product is rich in phenolics, flavonoids, alkaloids, and organosulfur compounds such as S-allyl cysteine, which are known to exhibit antioxidant, anti-inflammatory, and antimicrobial properties. This study aimed to determine the total alkaloid, flavonoid, and phenolic content, antioxidant activity, and acute toxicity profile of black garlic. Black garlic samples were prepared by fermenting Solo garlic for 12 days at 60–70 °C. Alkaloid content was analyzed spectrophotometrically using Bromocresol Green reagent with quinine as the standard, flavonoid content was determined using quercetin, and total phenolic content was measured using the Folin–Ciocalteu method with gallic acid as the standard. Antioxidant activity was assessed using the DPPH method, while acute toxicity testing was conducted on male BALB/c mice at doses of 500–5.000 mg/kg BW following OECD/GHS guidelines. The results showed that black garlic contained 301.65 ± 3.436 mg QE/kg alkaloids, 2.190 ± 0.051 mg QE/g flavonoids, and 81.976 ± 1.179 mg GAE/g phenolics. Antioxidant activity was categorized as very strong with an IC₅₀ value of 9.94 ± 0.012 ppm, comparable to Vitamin C (9.92 ± 0.005 ppm). Acute toxicity tests revealed no toxic symptoms or mortality up to 5.000 mg/kg BW, classifying black garlic as practically non-toxic. In conclusion, black garlic is rich in bioactive compounds, demonstrates strong antioxidant activity, and is safe for consumption, making it a potential functional food and health supplement.